Pendampingan Dalam Rangka Memperingati Hari Besar Islam (PHBI) Maulid Nabi Muhammad SAW - Abd Quddus Al Badani; M. Irwan Mansyuriadi (Indonesia, 2024)
Community service activities in the form of commemorating the Prophet Muhammad's Birthday aim to provide enlightenment to the community. about the history, and the struggle of the prophet and his companions in building Islamic civilization to be emulated. The method used in this community service activity with a collaborative-participatory dialogical approach includes in-house training, mentoring children before the peak event who will appear to fill PHBI such as reading short verses and practicing Islamic art performances. Furthermore, lectures, questions and answers, discussions. Participants in the community service program activities also consist of the general public or congregation from young to old, from men and women. The participants in this activity stated that this activity was very useful, because it could provide a lot of knowledge related to inspiring history and so on, but there were still many who felt they did not understand it optimally, especially those who rarely attended the ta'lim assembly or became participants in the study group. This community service activity can run well, smoothly and enthusiastically and even as a follow-up they have proposed material every time a meeting one theme is presented specifically.